Cocoa farmers’ perception regarding the effectiveness of cocoa extension services in the Bia West District, Ghana. - Tham-Agyekum, Enoch Kwame; Somed, Kassim; Appiah, Patrick; Asiamah, Maxwell Toah; Ankuyi, Fred; Appiah, Anthony; Bakang, John-Eudes Andivi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
The study analysed cocoa farmers’ perception on the effectiveness of agricultural extension services in the Bia West District. Data for the study was collected from 400 cocoa farmers through a multistage sampling technique. Data was analysed using both descriptive and inferential statistics. The results reflect a prevailing awareness among the majority of cocoa farmers (over 90%) concerning the efficacy of agricultural extension agents operating in the study area. Farmers perceived a positive impact on information dissemination and timeliness (Mean=4.08), and knowledge and skills enhancement (Mean=4.03). Employing a probit model, age (1%), engagement in off-farm activities (10%), and the age of cocoa farms (1%) emerged as significant factors that influenced farmers' perception of the effectiveness of the agents. The three key challenges faced by farmers in accessing extension services included inadequate CEA visits (1st), trust issues (2nd), and communication barriers (3rd). The study recommends the critical need to intensify and sustain extension training programmes, incentivising and supporting CEAs in fostering robust relationships within farming communities, and directing policy initiatives toward bolstering investments in communication infrastructure.